Philosophical Perspectives on Modern Marketing: An Analysis of Post-Covid-19 Dynamics and Strategic Adaptations - Susanto, Afif; Harsono, Mugi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This article employs a philosophical study of science to comprehensively examine the transformations in marketing behavior patterns triggered by the global impact of Covid-19. It integrates the dimensions of ontology, epistemology, and axiology to explore post-pandemic marketing dynamics. The research elucidates shifts in market realities and consumer experiences before and after the pandemic, exploring the mechanisms underlying these changes and providing insights into the evolving landscape of modern marketing. Emphasizing the imperative for organizations to continually reassess and adapt their strategies, the study underscores the importance of understanding the epistemological foundations of marketing paradigm shifts. Remaining attuned to market trends and technological advancements is deemed critical for relevance in the post-Covid-19 landscape. The research also highlights the significance of aligning modern marketing with consumer values in the “new normal,” urging organizations to integrate these values into their strategies for mutual benefits. This study offers valuable insights for organizations navigating and capitalizing on the evolving dynamics of marketing in the post-Covid-19 era.